Analisis Kohesi Gramatikal (Konjungsi) dalam Novel Ronggeng Dukuh Paruk Karya Ahmad Tohari - Aster Pujaning Ati (LITERATUS, 2020)
The purpose of this study was to determine the grammatical elements in the novel Ronggeng Dukuh Paruk by Ahmad Tohari. The grammatical elements taken are all elements of the conjunction. This research uses qualitative methods, because qualitative research is the most suitable research with literary phenomena. Analysis techniques (Content Analysis) are also used for discourse related to the content of novel discourse, both verbally and nonverbally; Verbal discourse in this study is a novel in which the total content of the discourse is meant. The complete sample of the contents of the Ronggeng Dukuh Paruk novel text is to use a sample of 2 stories from 3 stories. Each story the author will take 15 paragraphs for analysis. With a total of 30 paragraphs. Grammatical on the conjunction aspect shows the percentage of the use of grammatical cohesion in the conjunction aspect as many as 62 pairs of sentences or 60.78%.